Violet the carpenter / Amirul Hakimi Azni ... [et al.] - Azni, .Amirul Hakimi; Roslan, Muhammad Haziq Hariz; Zainol Arifen, Muhammad Zakwan; Ariffin, Ahmad Safwan (2022)
Violet The Carpenter company is a form of business based on partnership which consist of four members which hold important position such as General Manager, Administration Manager, Marketing Manager, Operational Manager and Financial Manager. The business capital is amounted to RM 100,000.00 where contribution of each member is RM 25,000.00. This company provides multi-purposes furniture using the pallet wood according to the customer design. Violet The Carpenter with motto of ‘Variety Of Ones’ is located at Ayer Keroh with address: No 17, Jalan KF4 Hang Tuah Jaya, Lingkaran Mitc, 75350 Melaka, Malaysia. Violet The Carpenter is a company which focuses on production of furniture in Malaysia. This company provided furniture which is wanted by the customer nowadays as it is easy to consume and have multi-function. Differences normal furniture design compared to our company design makes this furniture look more interesting and suitable with all sizes of houses especially for those with small houses as this product can fit even in small spaces. To make it more attractive we decided to make some innovation by implying our creativity and modern element in this furniture. We have done some research that Malaysia is one developed country which consist of the people with lower income level and higher income level. Thus, we recommended this furniture suitable with all type of income level as the prices of our furniture is reasonable and affordable